VD_FINDINFO Jug / 2021 / 29 vom 22. Mai 2020 - VD Tribunal cantonal (2020)
INJURE, INDEMNITÉEN GÉNÉRAL, FRAIS DE LA PROCÉDURE, ADMISSION PARTIELLE, PROCÉDURE ÉCRITE | 177 CP, 48 let. b CP, 426 al. 1 CPP (CH), 433 al. 1 CPP(CH)